Different taxation between diesel and gasoline: Is it justifiable for Portugal?. (June 2022) - Silva, Susana; Soares, Isabel; Pinho, Carlos
Abstract: We question the fiscal advantage enjoyed by diesel fuel in Portugal based on economic and environmental grounds. To do so, we estimate price and income elasticities for diesel and gasoline. Our results show that diesel consumption is inelastic to price changes in Portugal, and instead, this consumption is highly dependent on economic growth, given its strong use for commercial purposes. Consequently, higher taxes on diesel are not very effective to moderate demand and would hinder firm's competitiveness. To protect the environment other policy options should be explored, such as environmental standards and incentives to electric mobility.